2020
DOI: 10.3390/v12040458
|View full text |Cite
|
Sign up to set email alerts
|

Human West Nile Virus Lineage 2 Infection: Epidemiological, Clinical, and Virological Findings

Abstract: West Nile virus (WNV) lineage 2 is expanding and causing large outbreaks in Europe. In this study, we analyzed the epidemiological, clinical, and virological features of WNV lineage 2 infection during the large outbreak that occurred in northern Italy in 2018. The study population included 86 patients with neuroinvasive disease (WNND), 307 with fever (WNF), and 34 blood donors. Phylogenetic analysis of WNV full genome sequences from patients’ samples showed that the virus belonged to the widespread central/sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
(34 reference statements)
2
33
0
1
Order By: Relevance
“…Previous studies such one conducted in northeastern Italy in 2012, one in Greece in 2013 and another in Hungary in 2014, revealed positivity rates in urine samples of 43,8% (14/32), 40% (14/35) and 27,3% (3/11), respectively (Barzon et al, 2013a;Papa et al, 2014;Nagy et al, 2016). We also found that WNV RNA detection was more effective in urine samples than in CSF which con rms previous ndings (Barzon et al, 2015(Barzon et al, , 2013a(Barzon et al, , 2012Pacenti et al, 2020). While 50,5% of urine samples from our patient were positive, only one CSF, sampled on day 3 after symptom onset, was positive.…”
Section: Discussion/conclusionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies such one conducted in northeastern Italy in 2012, one in Greece in 2013 and another in Hungary in 2014, revealed positivity rates in urine samples of 43,8% (14/32), 40% (14/35) and 27,3% (3/11), respectively (Barzon et al, 2013a;Papa et al, 2014;Nagy et al, 2016). We also found that WNV RNA detection was more effective in urine samples than in CSF which con rms previous ndings (Barzon et al, 2015(Barzon et al, , 2013a(Barzon et al, , 2012Pacenti et al, 2020). While 50,5% of urine samples from our patient were positive, only one CSF, sampled on day 3 after symptom onset, was positive.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…Barzon et al Pacenti et al found that viral shedding in urine samples starts within the rst week after symptom onset then lasts up to 30 days(Barzon et al, 2012;Pacenti et al, 2020). In our series, WNV RNA could be detected in urine samples from 1 up to 41 days after symptom onset.…”
supporting
confidence: 61%
“…Last but not least, our data lack a significant information represented by the viral genotyping of the reported cases. According to available data, earlier reports on WNV in Italy were mostly associated with lineage 1 [ 45 ], with a subsequent cocirculation of lineage 1 and 2 between 2013 and 2018 [ 45 , 59 ], while the 2018 incidence peak was largely associated with infections by lineage 2 [ 59 ], which was the predominant pathogen during the European summer season 2018 [ 45 ]. In other words, without an appropriate tracking of incident cases also in terms of phylogenetic analysis, we could lose significant details, being eventually unable to properly track the actual spreading of WNV across Italy, possibly anticipating the emergence of human cases by properly identifying suitable reservoirs, and particularly certain species of migratory birds.…”
Section: Discussionmentioning
confidence: 99%
“…Serious manifestations of WNND include encephalitis, meningitis, and acute flaccid paralysis [42]. Additionally, some patients suffer fatigue, muscle weakness, and persistent tremors, lasting weeks to years even after recovery [43][44][45]. Unfortunately, only supportive treatment is available for patients who suffer from severe and debilitating effects of WNND.…”
Section: West Nile Virus (Wnv)mentioning
confidence: 99%